2020
DOI: 10.1111/ocr.12431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain intensity in patients treated with aligners and conventional fixed appliances: Randomized clinical trial

Abstract: Objective This randomized clinical trial aimed to compare the pain intensity in patients treated with orthodontic aligners and conventional fixed appliances. Setting and sample population This study was a randomized clinical trial. The sample comprised 39 patients randomly allocated into 2 groups: OA (orthodontic aligners, n = 20) and FA (Fixed Appliance, n = 19). Material and methods The pain intensity was measured by the visual analogue scale (VAS) in the following periods: T0 (baseline), T1 (seven days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
(145 reference statements)
2
13
0
Order By: Relevance
“…These results were found for both jaws, confirming that higher pain intensity leads to more frequent selfmedication. The frequency of self-medication with analgesics in this sample was comparable to previous studies [19][20][21] .…”
Section: Resultssupporting
confidence: 90%
“…These results were found for both jaws, confirming that higher pain intensity leads to more frequent selfmedication. The frequency of self-medication with analgesics in this sample was comparable to previous studies [19][20][21] .…”
Section: Resultssupporting
confidence: 90%
“…As in the present study, other authors obtained statistically significant differences when comparing pain scores between patients with aligners and patients with fixed multibracket appliances. In this study, patients with aligners indicated a lower level of pain compared to those in [34,35]. Fujiyama K et al also observed that patients with aligners described a lower level of pain in the first phases of orthodontic treatment compared to those with conventional fixed appliances.…”
Section: Discussionsupporting
confidence: 57%
“…According to the systematic review carried out by Long et al in 2013, the degree of pain that occurs in lingual orthodontic and conventional orthodontic treatments is similar [ 50 ]. In a randomized clinical trial recently published by Casteluci et al, where they compared the intensity of pain between fixed appliances and aligners, they concluded that it was similar and mild–moderate with both techniques [ 51 ]. The same happens between conventional fixed orthodontics and low friction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found no differences in pain intensity and age or sex of the patients in adult patients [ 14 , 26 , 46 , 57 , 58 ]. We can also add that this was a short-term study, the reason being that the first week was when patients felt the greatest pain and it decreased as months passed during orthodontic treatment [ 51 ]. Long-term studies are needed to see the different behavior that different orthodontic techniques may have in reference to periodontal pain.…”
Section: Discussionmentioning
confidence: 99%